Promising features of low-temperature grown Ge nanostructures on Si(001) substrates. (9th February 2017) - Wang, Ze; Wang, Shuguang; Yin, Yefei; Liu, Tao; Lin, Dongdong; Li, De-hui; Yang, Xinju; Jiang, Zuimin; Zhong, Zhenyang
Abstract: High-quality Ge nanostructures are obtained by molecular beam epitaxy of Ge on Si(001) substrates at 200 °C and ex situ annealing at 400 °C. Their structural properties are comprehensively characterized by atomic force microscopy, transmission electron microscopy and Raman spectroscopy. It is disclosed that they are almost defect free except for some defects at the Ge/Si interface and in the subsequent Si capping layer. The misfit strain in the nanostructure is substantially relaxed. Dramatically strong photoluminescence (PL) from the Ge nanostructures is observed. Detailed analyses on the power- and temperature-dependent PL spectra, together with a self-consistent calculation, indicate the confinement and the high quantum efficiency of excitons within the Ge nanostructures. Our results demonstrate that the Ge nanostructures obtained via the present feasible route may have great potential in optoelectronic devices for monolithic optical–electronic integration circuits.